Mental condition and career satisfaction in Malaysian government / Khalid Amin Mat, Siti Rapidah Omar Ali and Nur Shafini Mohd Said - Mat, Khalid Amin; Omar Ali, Siti Rapidah; Mohd Said, Nur Shafini
Changes in a government structure such as organization realign, redesign, restructure and downsize on an ongoing basis, affects the mental conditions of the workers to survive in the working environment. Besides workers have to cope with the increasing workloads after a few changes in government policies and at the same time the pressures of modern life. The element of threat in the career including job loss can be mentally devastating and may influence the mental well-being of the workers. Career satisfaction should be taken into consideration because workers usually spend more than 10 hours working in the workplace, facing work-related stress and can affect their mental conditions. The study is aim to investigate the correlation between career satisfaction and Health-Related Quality of Life (HRQOL): mental conditions in Malaysian Government. The study also aims to determine the significant differences between career satisfaction of public servants by gender, salary, age and working duration. Career satisfaction Questionnaire and WHOQOL-BREF Questionnaire were used as instruments to support theory for this research. The findings show meaning dimension scored the highest followed by competence, orientation, supervision, professionalization, work-related stress, and financial dimension in career satisfaction level among public servants. Career satisfaction was measured using self-reported by 215 employees from government agencies that was randomly selected from the sampling frame. As the result of the data analysis, the researchers found that the public servants were satisfied with their jobs in their overall level of career satisfaction. It is proven in this study that mental conditions among public servants are moderately influenced by career satisfaction. Further research is required to cover other factors that can also affect the career satisfaction level and at the same time close the current gaps in our understanding of career satisfaction and its relationship with HRQOL domain mental conditions.